Suplementação de lisina e metionina em associação ou não com o óleo de soja na dieta de vacas leiteiras - Helena Nogueira Frota (2011)
The objective of this study was to evaluate the effects of lysine and methionine supplementation with or without soybean oil in the diet of dairy cows on milk production and composition. Twelve Holstein cows were randomly distributed in a 4x4 latin squarein four consecutive experimental periods of 21 days each. The experimental diets were O+LM (diet with soybean oil, lysine and methionine added in the total mixed ration), OLM (diet with complex soybean oil/ lysine and methionine provided as top dressed), OS (diet with soybean oil provided as top dressed) and LM (diet with lysine and methionine provided as top dressed). The milk production, milk protein and milk fatproduction were not affected by the addition of lysine and methionine in association or not with soybean oil in the diet. The milk fat percentage, 3.5% fat-corrected milk and solids corrected milk were reduced with increasing soybean oil in the diet. The milk protein percentage increased in 0.14% (P 0.05) when soybean oil was added to the diet in presence of the lysine and methionine. Excretion of purine derivatives were reduced by the addition of soybean oil in the presence of amino acids by 1.47 mmol/l (P 0.05). The blood glucose concentration difference between coccygeal and mammary vein showed 2.58 mg/dl reduction for OS compared to LM (P 0.05). The results suggest protection effect of oil/lysine and methionine complex from the rumen degradation in this experimental condition.